Heavy Metal Content in Substrates in Agricultural Biogas Plants (Agricultural Engineering, 2023)
The content of heavy metals in soil should be continuously monitored, especially in organic crops. Exceeding the permissible concentrations of these elements may lead not only to inhibition of plant growth but also to ingestion into the organisms of animals that feed on these plants.Heavy metals usually enter the soil via precipitation or manure. There is a noticeable increase in interest in digestate for fields fertilization. Therefore, the authors decided to test the heavy metal content in substrates (slurry and solid input) and digestate. The 15x3 samples tested showed that only trace amounts of heavy metals were present. The study shows that the content of these elements in the digestate is not the sum of the elements supplied to the digester with the substrates. In most of the samples tested, lead concentrations did not exceed 5 mg‧kg−1. The lowest amounts of cadmium (an average of 0.28 mg‧kg−1) were observed in the slurry, and the highest (an average of 0.34 mg‧kg−1) in the solid substrate fed to the digester. Slurry had the lowest mercury and cadmium contents (average 0.012 mg‧kg−1and 5.8 mg‧kg−1). The highest concentration of chromium was registered in the digestate (average 3 mg‧kg−1) and this was on average 0.3 mg‧kg−1 higher than the feedstock and 0.5 mg‧kg−1 than the slurry